Chromaticity Investigation Of Curcuminoid Dye Composite For White Light Down-Conversion - Al Shafouri, Mahmood Shaikhan Ta’eeb (2020)
The main aim of the research work presented in this thesis was to produce white light using curcuminoid dye by simple and economical methods: curcuminoid phosphor with silicon rubber and Polymethyl methacrylate integrated curcuminoid nanofibers (PICNFs). This study also aimed to compare and improve the lifetime of white light by mitigating the degradation of curcuminoid dye in several ways, such as using a gap between the light source and phosphor layer or by annealing the nanofibers